REVOLUSI MENTALMEWUJUDKAN SISWA BERKEPRIBADIANMELALUI PENDIDIKAN AGAMA TERPADU - DEMINA DEMINA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
Mental revolution is a national movement that could be implemented in many areas including in the field of education. Teachers could implement this movement in order to inject students’ character. One of the strategies to actualize mental revolution in schools is using integrated Islamic teaching. Islamic teaching is not taught separately but must be implemented integratively. The use of integrative Islamic teaching is expected that students comprehend the learning content contextually. The implementation might be done using the integration of Islamic teaching to other subject matters such as civic, sport, art, language and others. It is even could be done the use of the integration of Islamic teaching to Islamic subject matters such as fiqh, aqidah akhlaq, and Quran hadits. The use of this integration is expected to solve students’ problems in their daily life.Kata kunci:revolusi mental, kepribadian, pendidikan agama terpadu